2000
DOI: 10.1002/(sici)1096-9071(200002)60:2<159::aid-jmv9>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of GB virus C/hepatitis G virus in Kinshasa, Democratic Republic Of Congo: A phylogenetic analysis

Abstract: A prevalence of 10.3% of GB virus C (GBV-C)/hepatitis G virus (HGV) carriers was found in 97 pregnant women from Kinshasa, Congo (formerly Zaire), while prevalences of 1%, 4.1%, and 0% were found for hepatitis C virus, human immunodeficiency virus, and human T-lymphotropic virus respectively. Phylogenetic analysis of the ten GBV-C/HGV positives based on the 5' non-coding region using three different methods identified consistently three GBV-C/HGV genotypes. Four main clades were found within the type 1 sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
4
9
1
Order By: Relevance
“…Globally, 1-4% of healthy blood donors are viremic for HPgV and another 13% carry anti-HPgV antibodies (Blair et al, 1998;Gutierrez et al, 1997;Pilot-Matias et al, 1996;Tacke et al, 1997). Here, we found HPgV RNA in 12.7% of samples, consistent with a previous survey that reported viremia in 10.3% of pregnant women in Kinshasa (Liu et al, 1999). We could not assess the frequency of HCV/HPgV co-infection because due to limited sample volume only those samples that were HCV seronegative were screened for HPgV.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Globally, 1-4% of healthy blood donors are viremic for HPgV and another 13% carry anti-HPgV antibodies (Blair et al, 1998;Gutierrez et al, 1997;Pilot-Matias et al, 1996;Tacke et al, 1997). Here, we found HPgV RNA in 12.7% of samples, consistent with a previous survey that reported viremia in 10.3% of pregnant women in Kinshasa (Liu et al, 1999). We could not assess the frequency of HCV/HPgV co-infection because due to limited sample volume only those samples that were HCV seronegative were screened for HPgV.…”
Section: Discussionsupporting
confidence: 87%
“…Laurent et al (2001) surveyed pregnant women and commercial sex workers (CSW) in Kinshasa and reported seroprevalences of 6.6% among CSW and 4.3% among pregnant women. Liu et al (1999) also investigated pregnant women from Kinshasa (n = 97) and found that while 10.3% carried human pegivirus (HPgV) RNA, only 1% carried HCV RNA. Most recently, Batina Agasa et al (2010) screened 140 patients with sickle-cell disease in Kisangani for anti-HCV antibodies and found 7.9% were seropositive, all of whom had received blood transfusions before the introduction of HCV screening in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…1997 ). The results from Brazil are comparable to prevalences in Congo or South Africa ( Liu et al . 1999 ; Casteling et al .…”
Section: Discussionsupporting
confidence: 82%
“…In healthy Kuwaitian, Jordanian and Tunisian blood donors the HGV prevalence of 24.6; 9.8% and 5.3%, have been reported, respectively 20,21. In central Africa, HGV prevalence of 10.3% and 12.6% was also found among pregnant women 22,23…”
Section: Discussionmentioning
confidence: 99%